PREVALENCE AND KNOWLEDGE OF FOOD ALLERGY AMONG FIFTH SEMESTER MEDICAL STUDENTS IN UDAYANA UNIVERSITY, DENPASAR, BALI - Selvanathan, Siva Jothiswari (E-Jurnal Medika Udayana, 2018)
This research was mainly done to find out the prevalence and knowledge of food allergic reaction among fifth semester Faculty of Medicine students of Udayana University. Food allergy is defined as an adverse immunologic response to food protein that leads to variety of clinical symptoms. Food allergy has emerged as an important public health problem based on its increasing prevalence, which has become the background for this research. Fifth semester medical students of Udayana University was chosen as the subject on whom this research was conducted. The method of observational descriptive study with the cross-sectional approach was carried out to find out the prevalence as well as the knowledge they have regarding food allergic reaction. Total sampling technique was used followed by questionnaire distribution and finally data collection and analysis were carried out. As for the results, in terms of prevalence 23.5% which is 23 students out of 115 students seems to have experienced food allergic reaction. As for knowledge, the cross-sectional result of allergic experience and knowledge showed 16.5% seems to have good knowledge over 23.5%. The results showed that, the aim of this research was achieved where students do have good knowledge about food allergic reaction and are capable in educating their patients in the future. This research hopefully would create an urge among students to take precaution regarding the emerging of food allergic reaction cases. Keywords : prevalence, knowledge, food allergic reaction, students, research